Seçici serotonin gerialım inhibitörü kullanan hastalarda cyp2c19 polimorfizmleri ile advers ilaç reaksiyonu ve hasta uyuncu ilişkisi - Deniz, Semanur (My University, 2013)
1. ÖZET Çalışmamızda, Haydarpaşa Numune Eğitim ve Araştırma Hastanesi Psikiyatri Polikliniği’nden majör depresyon tanısı alıp; sertralin, sitalopram veya essitalopram gibi seçici serotonin gerialım inhibitörü kullanan 53 hastada sitokrom P-450 2C19 (CYP2C19) enzim polimorfizmleri ile advers ilaç reaksiyonları ve hastaların tedaviye uyuncu arasındaki ilişkinin belirlenmesi amaçlanmıştır. Hastalardan toplanan periferik kan örneklerinden ilk olarak DNA izolasyonu yapılmıştır. Polimorfizmler, genomik DNA’dan Real-Time Polimeraz Zincir Reaksiyonu yöntemiyle belirlenmiştir. Advers etkiler, “Toronto Yan Etki Ölçeği”; hastaların tedaviye uyuncu “Morisky Uyum Ölçeği” ile değerlendirilmiştir. Bulgular değerlendirildiğinde, hastaların %54.7’sinin sersemlik/ gündüz uykuya eğilim, %43.4’ünün halsizlik veya yorgunluk, %43.4’ünün terleme, %41.5’inin bulantı ve %41.5’inin ağız kuruluğu advers etkilerini yaşadıkları saptanmıştır. Tedaviye uyuncu yüksek olan hasta sayısı 9 (%17) olarak bulunmuştur. Saptanan CYP2C19 polimorfizmlerine göre hastaların %37.7’si orta hızlı, %24.5’i hızlı, %20.8’i ultra hızlı metabolizer olarak sınıflandırılmıştır. CYP2C19*17 allel sıklığı %24.5, CYP2C19*2 allel sıklığı %27.35 olarak saptanmıştır. Hızlı metabolizer bireyler ile kıyaslandığında, ortalama advers ilaç reaksiyonu skorları orta hızlı fenotipli bireylerde daha yüksek, ultra hızlı fenotipli bireylerde ise daha düşük skorlarda bulunmuş; ancak aralarındaki fark istatistiksel olarak anlamlı bulunmamıştır. Ortalama uyunç skorları ve fenotip arasındaki ilişkilendirmede de benzer sonuçlar bulunmuştur. Yine ortalama advers etki skorları düşük olan bireylerin daha uyunçlu olduğu görülmüşse de; istatistiksel olarak gruplar arasında anlamlı fark bulunmamıştır. Anahtar Sözcükler: advers ilaç reaksiyonu, CYP2C19 polimorfizmleri, majör depresyon, uyunç 2.

Relationship between CYP2C19 Polimorphisms, Adverse Drug Reaction, and Medication Adherence in Patients Utilized Selective Serotonin Reuptake Inhibitors The aim of the study is to determine the relationship between cytochrome P-450 2C19 (CYP2C19) enzymes polymorphisms, adverse drug reactions, and medication adherence in 53 patients who were diagnosed with major depression at the Haydarpaşa Numune Training and Research Hospital Psychiatry Department and utilized selective serotonin reuptake inhibitor such as sertraline, citalopram or escitalopram. DNA isolation was made from the blood samples collected from the patients. Polymorphisms were determined from genomic DNA by using ‘Real-Time Polymerase Chain Reaction’ method. “Toronto Side Effects Scale” was used to determine the adverse drug reaction and also “Morisky’s Questions (Self-Report Measure of Adherence)” was used to assess patients’ medication adherence. The most common adverse drug reactions that patients reported were drowsiness/ day time somnolence (54.7%), malaise or fatigue (43.4%), sweating (43.4%), nausea (41.5%) and dry mouth (41.5%). Only nine (17%) patients were found adherent to their medication on the high level. When CYP2C19 polymorphisms were assessed, 37.7%, 24.5% and 20.8% of the patients were classified as intermediate, extensive and ultra-rapid metabolizers; respectively. Allele frequencies of CYP2C19*17 and CYP2C19*2 was calculated as 24.5% and 27.4%; respectively. When compared with individuals with extensive metabolizers, it was found higher adverse drug reaction scores in individuals with intermediate phenotype and lower adverse drug reaction scores in individuals with ultra-rapid phenotype, but these differences were not statistically significant (p>0.05). Similar results were obtained when the association between average adherence scores and phenotype was evaluated. Although patients with lower adverse drug reaction scores were more adherent to their medications; no statistically significant difference were found between the groups (p>0.05). Key Words: adherence, adverse drug reaction, CYP2C19 polymorphisms, major depression
Keywords: Depresyon; Farmakoloji; Hastalıklar; İlaçlar; İlaçlar_Tedavi; Majör; Psikiyatri